2005
DOI: 10.1002/cne.20553
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and immunohistochemistry of efferent neurons of the goldfish corpus cerebelli

Abstract: In teleosts, cerebellar efferent neurons, known as eurydendroid cells, are dispersed within the cerebellar cortex rather than coalescing into deep cerebellar nuclei. To clarify their morphology, eurydendroid cells were labeled retrogradely by biotinylated dextran amine injection into the base of the corpus cerebelli. Labeling allowed the cells to be classified into three types-fusiform, polygonal, and monopolar-depending on their somal shapes and numbers of primary dendrites. The fusiform and polygonal type ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 32 publications
2
63
0
1
Order By: Relevance
“…10), in agreement with former studies of the goldfish CC [Brochu et al, 1990;Ikenaga et al, 2005]. After large-dose injections of FG into the dcC, we observed many labeled cell bodies in the GGL of the vcC (Fig.…”
Section: Double Labeling With Fg and Immunohistochemistry For Zebrin IIsupporting
confidence: 81%
See 1 more Smart Citation
“…10), in agreement with former studies of the goldfish CC [Brochu et al, 1990;Ikenaga et al, 2005]. After large-dose injections of FG into the dcC, we observed many labeled cell bodies in the GGL of the vcC (Fig.…”
Section: Double Labeling With Fg and Immunohistochemistry For Zebrin IIsupporting
confidence: 81%
“…To better understand the organization of the cerebellar circuitry involved in the processing of descending telencephalic information from the input stage to the output stage, we injected tracers into the ML of the dcC and the vcC in Nile tilapia. We further confirmed PuC projections from the vcC to the dcC via double immunofluorescence labeling for zebrin II [aldolase C; Ahn et al, 1994], which is a specific marker for PuC in teleosts as well as mammals [Brochu et al, 1990;Sillitoe et al, 2004;Sugihara and Shinoda, 2004;Ikenaga et al, 2005].…”
Section: Abbreviations Used In This Papermentioning
confidence: 61%
“…Several features of the local cerebellar circuitry that are described here for the mormyrid central lobes are also present in the cerebellums of other teleosts (Finger, 1983;Ikenaga et al, 2005;Meek, 1998;Murakami and Morita, 1987;Pouwels, 1978). Thus, in other teleosts as in mormyrids: a) climbing fibers terminate within the largecelled ganglionic layer of the cortex and do not enter the molecular layer; b) the dendrites of both Purkinje cells and efferent cells are fan-like and oriented in parasagittal planes perpendicular to the parallel fibers; and c) most Purkinje cell axons do not leave the cortex but terminate locally on efferent cells, other Purkinje cells, and deep stellate cells.…”
Section: Comparisons With the Cerebellum Of Other Teleostsmentioning
confidence: 89%
“…nopterygii; Finger, 1983;Ikenaga et al 2005;Lannoo et al 1991;Meek, 1998). Besides these anatomical features, the mormyrid cerebellum is also of interest because of its involvement in the active electrosensory system of these fish, a system with several advantages for studying cerebellar function.…”
mentioning
confidence: 99%
“…Only a few of them express the Purkinje cell marker zebrin II [Lannoo et al, 1991] and GABA-synthesizing enzymes gad65/67a,b, whereas many express calretinin [Castro et al, 2006b]. These features suggest that dlx5a-6a:GFP+ cells in the zebrafish cerebellum are eurydendroid neurons, the equivalent in the fish of the neurons of the DCN that project outside of the cerebellum [Ikenaga et al, 2005;Nieuwenhuys, 1988]. Indeed, recent studies in the mouse have shown that glutamatergic neurons of the DCN are generated in the upper RL [Wang et al, 2005], rather than in the cerebellar ventricular zone as hypothesized by classical lineage studies.…”
Section: Migration Of Cerebellar Neuronmentioning
confidence: 90%